2000
DOI: 10.1128/mcb.20.20.7773-7783.2000
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Telomere Distribution and Sertoli Cell Nuclear Architecture Are Altered in Atm- andAtm-p53-Deficient Mice

Abstract: The ataxia telangiectasia mutant (ATM) protein is an intrinsic part of the cell cycle machinery that surveys genomic integrity and responses to genotoxic insult. Individuals with ataxia telangiectasia as well as Atm ؊/؊ mice are predisposed to cancer and are infertile due to spermatogenesis disruption during first meiotic prophase. Atm ؊/؊ spermatocytes frequently display aberrant synapsis and clustered telomeres (bouquet topology). Here, we used telomere fluorescent in situ hybridization and immunofluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
79
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 97 publications
0
79
0
Order By: Relevance
“…One possible interpretation for the accumulation of spermatocytes I with bouquet topology in Atm de®cient cells could be slow progression through initial stages of ®rst meiotic prophase and an ensuing arrest and demise of spermatocytes I. Sertoli cells contribute to faithful spermatogenesis. In the Atm-mutants, sertoli cells were found to frequently display numerous heterochromatin-and telomere clusters ± a nuclear topology which resembles that of immature sertoli cells (Scherthan et al, 2000). Atm disruption causes an immature nuclear architecture/heterochromatin distribution in sertoli cells, the supportive somatic cell lineage of the seminiferous epithelium; which display strong immunouorescent Atm signals in their chromatin.…”
Section: Atm De®ciency In¯uences Telomere Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible interpretation for the accumulation of spermatocytes I with bouquet topology in Atm de®cient cells could be slow progression through initial stages of ®rst meiotic prophase and an ensuing arrest and demise of spermatocytes I. Sertoli cells contribute to faithful spermatogenesis. In the Atm-mutants, sertoli cells were found to frequently display numerous heterochromatin-and telomere clusters ± a nuclear topology which resembles that of immature sertoli cells (Scherthan et al, 2000). Atm disruption causes an immature nuclear architecture/heterochromatin distribution in sertoli cells, the supportive somatic cell lineage of the seminiferous epithelium; which display strong immunouorescent Atm signals in their chromatin.…”
Section: Atm De®ciency In¯uences Telomere Clusteringmentioning
confidence: 99%
“…Recent studies have shown that ATM is associated with chromatin (Gately et al, 1998;Scherthan et al, 2000) and a fraction of the ATM is detected in nuclear aggregates (Andegeko et al, 2001). The striking correlation between the appearance of retained ATM and of histone H2AX (?-H2AX), and the rapid association of a fraction of ATM with ?-H2AX foci, are consistent with a major role for ATM in the early detection of DSBs and subsequent induction of cellular responses.…”
Section: Atm De®ciency In¯uences Telomere Chromatin Structurementioning
confidence: 99%
“…After air drying, slides were stored at Ϫ20°C until further use. Immunofluorescent staining was done as described previously (24,67).…”
mentioning
confidence: 99%
“…Telo-FISH was combined with IF. This was achieved by first performing immunostaining and then preparations were subjected to simultaneous denaturation in the presence of the telomere probe (Scherthan et al, 2000). Labeling, FISH and detection of oligonucleotides were performed as described (Scherthan et al, 2000).…”
Section: Meiotic Chromosome Preparations Immunocytochemistry and Flumentioning
confidence: 99%
“…Generally, mice of about 4 months of age, were killed and testes resected for further processing or instant snap freezing in liquid nitrogen. Structurally preserved suspension nuclei were prepared by crosslinking fixation with PBS-buffered formaldehyde (Scherthan et al, 2000). A polyclonal rabbit anti-SCP3 antiserum was utilized to detect axial cores and complete SCs .…”
Section: Meiotic Chromosome Preparations Immunocytochemistry and Flumentioning
confidence: 99%